Encryption and Decryption of Data - Verma, Gaurav (My University, 2007)
The selective application of technological and related procedural safeguards is an important responsibility of every organization in providing adequate security to its electronic data systems. This work specifies a cryptographic program which may be used bty organizations to protect sensitive data. Protection of data during transmission or while in storage may be necessary to maintain the confidentiality and integrity of the information represented by the data. The program developed in this work, emphasizes on the key and mixing with the data. The program users 64 bit key length. Initially the bits are subjected to permutation which produces a new pattern of bits and then further undergo modulo-2 addition, which produces a new key different from the key that was initially entered. This system is being made available for use by organizations within the context of a total security program consisting of physical security procedures, good information management practices, and computer system/network access controls.
Keywords: Computer network; Networing; Encryption of data; Computer science